Maternal concentration of polychlorinated biphenyls and dichlorodiphenyl dichlorethylene and birth weight in Michigan fish eaters: a cohort study - Zhu Xiaobei; Karmaus Wilfried (BMC, 2004)
Abstract Background Studies on maternal exposure to polychlorinated biphenyls (PCBs) reported inconsistent findings regarding birth weight: some studies showed no effect, some reported decreased birth weight, and one study found an increase in weights. These studies used different markers of exposure, such as measurement of PCBs in maternal serum or questionnaire data on fish consumption. Additionally maternal exposures, such as dichlorodiphenyl-dichloroethylene (DDE), which are related to PCB exposure and may interfere with the PCB effect, were rarely taken into account. Methods Between 1973 and 1991, the Michigan Department of Community Health conducted three surveys to assess PCB and DDE serum concentrations in Michigan anglers. Through telephone interviews with parents, we gathered information on the birth characteristics of their offspring, focusing on deliveries that occurred after 1968. We used the maternal organochlorine (OC) measurement closest to the date of delivery as the exposure. Although one mother may have contributed more than one child, serum concentrations derived from measurements in different surveys could vary for different children from the same mother. The maternal DDE and PCB serum concentrations were categorized as follows: 0 -< 5 microg / L, 5 -< 15 microg / L, 15 -< 25 microg / L, ≥25 microg / L. Using repeated measurement models (Generalized Estimation Equation), we estimated the adjusted mean birth weight controlling for gender, birth order, gestational age, date of delivery as well as maternal age, height, education, and smoking status. Results We identified 168 offspring who were born after 1968 and had maternal exposure information. We found a reduced birth weight for the offspring of mothers who had a PCB concentration ≥25 microg / L (adjusted birth weight = 2,958 g, p = 0.022). This group, however, was comprised of only seven observations. The association was not reduced when we excluded preterm deliveries. The birth weight of offspring was increased in women with higher DDE concentrations when controlling for PCBs; however, this association was not statistically significant. Conclusion Our results contribute to the body of evidence that high maternal serum PCB concentration may reduce the birth weight in offspring. However, only a small proportion of mothers may actually be exposed to PCB concentrations ≥25 microg / L.